CRYPTOCURRENCY IN THE MODERN ECONOMY - A.K. Sembekov, (Academic Journal of Physical and Chemical Sciences, 2019)
The article examines the economic content of crypto currency, capitalization issues and basic requirements for investment. The author conducted a comparative analysis of the dynamics of capitalization of the 10 largest crypto currencies for 2017 and 2018. The problems of crypto currencies, the complexity of their implementation and use in the modern economy are identified, the risks that have an impact on the development of the crypto currency market are identified. On the basis of the analysis the relevant conclusions are made. It should be noted that the study of methods of development of the crypto currency market in foreign countries is necessary for the possible use of their experience with the most effective solutions in the preparation of General principles of state regulation.